Legal analysis on human trafficking victims working as sex workers in Malaysia / Alia Nabilla Rizal Affendy … [et al.] - Rizal Affendy, Alia Nabilla; Mohd Kieron, Mohd Mifzal; Ahmad Zahar, Johan Radzi; Suliman, Nur Hani (2014)
Human trafficking is one of the biggest crimes globally, and sex-trafficking is one of its branches. As Malaysia is a developing country, the problem regarding prostitution under the human trafficking (or sex-trafficking) is getting more serious where we had been downgraded to the 3-tier by the US Report on Human Trafficking in 2014. In this research, we are discussing the problem within the context of prostitution activities, mainly by human trafficking victims. The victims are mostly trafficked by way of force, threat or fraud. In this research, we are mainly discussing upon the legislation in our country for the three part of the matter, i.e. the prosecution, the protection and also the prevention. The United Kingdom's Sexual Offences Act 2007 and also the Swedish Penal Code are also being compared to our law to recognise the lacunae. Generally, prostitution is an illegal activity, but when we are talking about the prostitutes who were forced into the prostitution, there is no clear protection upon them by the legislator where in most cases non-governmental organizations would come into the picture after the prosecution of the victims.